The lions of lucerne ebook - Thor, Brad (Scot Harvath, 2003)
In his daring and chilling first novel, #1 New York Times bestselling author Brad Thor draws us into a sinister labyrinth of political intrigue and international terrorism, serving up an explosive cocktail of unrelenting action as one man is pushed to the edge. On the snow-covered slopes of Utah, the President of the United States has been kidnapped and his Secret Service detail massacred. Only one agent has survived—ex-Navy SEAL Scot Harvath. He doesn't buy the official line that Middle Eastern terrorists are behind the attack and begins his own campaign to find the truth and exact revenge. But now, framed for murder by a sinister cabal, Harvath takes his fight to the towering mountains of Switzerland—and joins forces with beautiful Claudia Mueller of the Swiss Federal Attorney's Office. Together they must brave the subzero temperatures and sheer heights of treacherous Mount Pilatus—where their only chance for survival lies inside the den of the most lethal team of professional killers the world has ever known...